Consumption profile of functional probiotic foods: an analysis with students at the Federal University of Sergipe - UFS (Research, Society and Development, 2021)
The food industry has been increasing investment in researchers and technologies aimed at metabolic, physiological and beneficial effects on consumer health. The use of food as a vehicle to promote well-being and health and to reduce the risk of some diseases has encouraged research into new natural components and the development of new ingredients. Thus, the objective of this work is to analyze the profile of students at the Federal University of Sergipe-UFS in relation to the consumption of functional probiotic foods. The method used in this research was Survey, a field research type through the application of an online questionnaire with 10 closed questions, structured in the following sequence: 1) Analysis of the socioeconomic profile of the respondent; 2) Lifestyle analysis and 3) Check if the respondent has knowledge and habit of consuming probiotic foods. The survey results identified that young students are more concerne with getting healthier habits, most of them have a family income of 2 to 4 minimum wages, have a preference for individual sport (swimming, surfing, Pilates, walking), are aware of the which would be a probiotic food, prefer to consume respectively pasty foods (yoghurt, fermented milk and cheese), solids (food supplements in capsules, cereals, chocolate and whole grain bread) and liquid types (teas, soy milk or supplements). In conclusion, it could be identified that a considerable part of students adhere to the consumption of functional probiotic foods in order to maintain healthy lifestyle habits, increasing physical and mental well-being.